2021
DOI: 10.1002/mp.15096
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: On the feasibility of performing dosimetry in target and organ at risk using polymer dosimetry gel and thermoluminescence detectors in an anthropomorphic, deformable, and multimodal pelvis phantom

Abstract: Objective To assess the feasibility of performing dose measurements in the target (prostate) and an adjacent organ at risk (rectum) using polymer dosimetry gel and thermoluminescence detectors (TLDs) in an anthropomorphic, deformable, and multimodal pelvis phantom (ADAM PETer). Methods The 3D printed prostate organ surrogate of the ADAM PETer phantom was filled with polymer dosimetry gel. Nine TLD600 (LiF:Mg,Ti) were installed in 3 × 3 rows on a specifically designed 3D‐printed TLD holder. The TLD holder was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…If the delivery under evaluation involves motion management, then the phantom will have to be able to be integrated into some commercial or in-house built motion testing system [129,130,178,179]. For some RT deliveries the E2E QA phantoms may need to be more anthropomorphic in external appearance (e.g., if the delivery requires phantom set-up in some patient immobilization system with set-up validation and repositioning) or to simulate internal structure heterogeneity with organ mimicking structures (e.g., if the E2E testing is being applied to RT delivery to specific anatomy and the assessment includes target conformity) [89,102,104,106,111,180,181]. The material for the phantom need not be exactly tissue or water equivalent although it should be similar to any organs of interest and should be well characterised by CT, and perhaps MR imaging, before use [174].…”
Section: Implementing In-house E2e Testing Into a Clinical Qm Programmentioning
confidence: 99%
“…If the delivery under evaluation involves motion management, then the phantom will have to be able to be integrated into some commercial or in-house built motion testing system [129,130,178,179]. For some RT deliveries the E2E QA phantoms may need to be more anthropomorphic in external appearance (e.g., if the delivery requires phantom set-up in some patient immobilization system with set-up validation and repositioning) or to simulate internal structure heterogeneity with organ mimicking structures (e.g., if the E2E testing is being applied to RT delivery to specific anatomy and the assessment includes target conformity) [89,102,104,106,111,180,181]. The material for the phantom need not be exactly tissue or water equivalent although it should be similar to any organs of interest and should be well characterised by CT, and perhaps MR imaging, before use [174].…”
Section: Implementing In-house E2e Testing Into a Clinical Qm Programmentioning
confidence: 99%
“…The experiment was carried out using the so-called ADAM-PETer (Anthropomorphic, Deformable And Multimodal pelvis phantom with positron emission tomography (PET) Extension for Radiotherapy), which was initially designed to perform a variety of different end-to-end tests in radiotherapy (Gillmann et al 2021, Marot et al 2021. In the present study, however, no PET measurements were performed and the included lymph node system was not used.…”
Section: Phantommentioning
confidence: 99%
“…Other studies have suggested the use of thermoluminescence detectors (TLDs) to renormalize the absolute PG dose distribution (Mann et al 2019, Schwahofer et al 2020 as well as to combine PG and TLDs for dose measurements within the updated version of the ADAM phantom (ADAM-PETer, Marot et al (2021)). Marot et al (2021) applied the same phantom as used in the present study equipped with a PG-filled prostate and TLDs in the rectum. However, the phantom was used only statically without employing MR-guidance or online adaption of the treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the luminescence properties of inorganic rare‐earths compounds have been widely studied, [ 17–21 ] there is practically no information on the TL of lanthanide coordination compounds, although there is available information on TL in organic compounds, as well as in polymers. [ 22–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the luminescence properties of inorganic rare-earths compounds have been widely studied, [17][18][19][20][21] there is practically no information on the TL of lanthanide coordination compounds, although there is available information on TL in organic compounds, as well as in polymers. [22][23][24][25] Previously, we obtained interesting coordination compounds of terbium and dysprosium, which are able to store the energy from ultraviolet (UV) and X-ray radiation. [26,27] The energy from UV and X-ray radiation stored by these materials can be stored indefinitely at a low temperature even if the external excitation is removed.…”
Section: Introductionmentioning
confidence: 99%